Comparison of balance and stabilizing trainings on balance indices in patients suffering from nonspecific chronic low back pain - Mohammad Hosseinifar; Asghar Akbari; Maher Mahdavi; Maliheh Rahmati (Wolters Kluwer Medknow Publications, 2018)
The objective of the current research was to compare the impact of balance and stabilizing trainings on balance indices in patients with nonspecific chronic low back pain. In this randomized, controlled, single-blinded clinical trial, 20 people suffering from nonspecific chronic low back pain were randomly assigned to two groups of balance and stabilizing trainings. Trainings of both groups were performed for 6 weeks and four sessions per week. The overall, lateral, and anterior-posterior stability indices, pain, and disability were measured using Biodex balance system, visual analog scale, and Oswestry scale, before and after treatment, respectively. Paired t-test and independent t-test were used for analyzing the data. In the balance group, the pain severity was changed from 6.33 ± 1.63 to 4.33 ± 2.6 (P = 0.005) and dynamic anterior-posterior stability index in the standing position on left leg with closing eyes was changed from 5.56 ± 2.25 to 3.45 ± 1. 57 (P = 0.03). In the stabilizing group, pain severity was changed from 4. 16 ± 1.47 to 1.33 ± 0.81 (P = 0.0001) and disability index was changed from 17.33 ± 5.60 to 5.33 ± 3.93 (P = 0.01). Reduction in pain and disability in the stabilizing group and increase in two balance indices were significant in the balance training group compared to those in other group (P < 0.05). Research findings revealed that the impact of stabilizing trainings was significant in reducing pain and disability compared to that in balance trainings.